New highly fluorescent phthalocyanines dendrimers with fluorenyl-based connectors vs phenyl-based connectors. (22nd January 2022) - Ben Hassine, Sarra; Abid, Seifallah; Jamoussi, Bassem; Paul-Roth, Christine O.
Abstract: The design of dendrimers featuring conjugated fluorenyl dendrons via new connectors allows evaluating the importance of the role of these junctions and the nature of the core, on the optical properties of interest. In the continuation of our sustained interest for dendrimers and their use as luminescent labels for bioimaging, we wondered about the effect of changing the central porphyrin core for a phthalocyanine one in these macromolecular structures. Thus, a related phthalocyanine-based dendrimer possessing up to eight conjugated 9, 9-dibutyl-2-fluorenyl endgroups was designed, and for the first time, these endgroups are linked to the central phthalocyanine core by new fluorenyl-based connectors C2 instead of the more classic 1, 3, 5-phenylene one C1 . This original dendrimer was characterized and studied and as for porphyrin analogues, it was found that an efficient energy transfer occurs from the peripheral fluorenyl units to the central phthalocyanine core, leading to an intense red light emission. The luminescence is improved compared to that of their porphyrin-cored analogues for bioimaging, evidencing the key role played by the central core in this respect and the nature of the connector Cn . The impact of the structural changes of the core in relation with the impact resulting from the changes in dendron connectors is discussed. Graphical abstract: Image 1